Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Kognitif Anak Usia 4-5 Tahun di TKN Beiposo - Andi Nafsia; Gde Putu Arya Oka; Karmelia Rosfinda Meo Maku; Emiliana Serlinda Wona Muku (CV. Ulil Albab Corp, 2026)
The urgency of this study lies in the need for an empirical understanding of the extent to which parenting styles are related to children's cognitive development, particularly in the environment of TKN Beiposo. This study employed a quantitative approach with a correlational research design. The population consisted of all children aged 4-5 years and their parents. The sampling technique used was saturated sampling, chosen because the population size was relatively small. In quantitative research, the instruments must meet the requirements of validity and reliability. The reliability test obtained a Cronbach’s alpha value of 0.709, indicating that the instrument used in this study is reliable. Therefore, the research instrument has fulfilled the requirements of validity and reliability and is appropriate to be used to test the research hypothesis.